Soil organic carbon, carbohydrates, amino sugars, and potentially mineralizable nitrogen under different land-use systems in oxisols of the Brazilian cerrados - Fuhrmann, S; Neudelft, H; Westerhof, R; Ayarza, Miguel Angel; Silva, J.E. da; Zech, W. (International Center for Tropical Agriculture, 1999)
Intensive farming and grazing on Oxisols of the Brazilian savannas (also known as the Cerrados) are leading to loss of soil organic matter (SOM) and consequently to a decline in fertility and sustainability of the soils. Alternative land-use systems such as the introduction of legumes in pastures and the use of no-tillage systems can reverse this process. In this study, the effects of seven land-use systems (native savanna, forest, degraded pasture, improved pure-grass pasture, improved grass/legume pasture, conventional cropping, and no-tillage cropping) on the SOM and potentially mineralizable nitrogen (Npo) were examined in whole-soil samples and particle-size separates. In addition, sugars and amino acids were determined for a better understanding of SOM dynamics. Compared with native savanna, soil organic carbon (SOC), cellulosic and noncellulosic polysaccharides (CPs and NCPs, respectively), amino sugars, and Npot decreased under forest and increased under pastures. The positive influence of improved pasture systems, especially the grass/legume pasture, was clearly recognizable. Under the no-tillage system, SOC and Npot levels increased, compared with conventional tillage. These differences were clearest in the sand fractions of the particle-size separates. The sugar dynamics reflected decomposition of plant tissue and subsequent accumulation of microbial sugars. The ratio of glucosamine to muramic acid increased from coarse sand to fine sand and thereafter decreased toward clay. The cause may be a stronger association of fungal hyphae with fine roots in the fine-sand fraction and an increased association of bacteria with the clay fraction. Amino sugars appeared to be an important source of Npot.